Assessment of different Enzymatic Virulence Traits contributing to pathogenicity of Candida Albicans - Nazeer, Sadia; Afshan Naz, Sehar; Zubair, Arif; Shafique, Maryam; Sharafat, Shaheen; Baig, Samina; Gul Jabeen (International Journal of Endorsing Health Science Research, 2023)
Background: Candidiasis is regarded as one of the frequently occurring fungal infections of humans elicited by yeast that belongs to the genus Candida. Among the different species of Candida, Candida albicans is the most pathogenic specie. The pathogenicity of this specie depends on various virulence factors. This study was designed to determine the activity of some important enzymatic virulence factors such as phospholipase, proteinase and hemolysin produced by Candida albicans strains. Methodology: A total of 300 clinical isolates of C. albicans were obtained and identified by conventional standard diagnostic criteria. For the evaluation of phospholipase production, the egg yolk agar medium was employed. The minimum agar medium was used for proteinase activity and for hemolysin production, blood plate assay was used. The results were statistically analyzed by SPSS 16.0 version software. Results: Of a total of 300 isolates reviewed, the majority of the isolates were recovered from females, i.e. 234 (78%); however, the number of isolates obtained from males were 66 (22%). Amongst all the strains of C. albicans, phospholipase and hemolysin enzymes were produced primarily by 89.3% of the total C. albicans strains. While proteinase enzyme was produced by 86% of the total C. albicans isolates. A p-value < 0.05 was measured as statistically significant. Conclusion: From the existing study, it can be determined that these enzymes are produced by most of the pathogenic strains of C. albicans. The detection of these virulence enzymes is tremendously significant in designing of drugs to combat these opportunistic infections in future.